2020
DOI: 10.1177/0363546520908847
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Stem Cell–Derived Exosomes Decrease Fatty Infiltration and Enhance Rotator Cuff Healing in a Rabbit Model of Chronic Tears

Abstract: Background: Fatty infiltration and poor tendon-bone healing in chronic rotator cuff tears (RCTs) are associated with unsatisfactory prognosis. Adipose stem cell–derived exosomes (ASC-Exos), having multiple biological effects, can prevent muscle degeneration in acute RCTs. However, the effects of ASC-Exos on fatty infiltration and tendon-bone healing in chronic RCTs remain unknown. Purpose: To study the effects of ASC-Exos on fatty infiltration and tendon-bone healing in a chronic RCT rabbit model. Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 38 publications
3
128
0
Order By: Relevance
“…However, Zhang et al 77 demonstrated the e cacy of human embryonic MSC exosomes in promoting cartilage regeneration, and the utility of MSC exosomes as a ready-to-use and "cell-free" therapeutic alternative to cell-based MSC therapy in vivo. As for BTI healing, Wang et al 71 showed that adipose stem cell-derived Exos can decrease fatty in ltration and enhance BTI healing in vivo. In accordance with Wang et al 71 research, the present study also revealed improved BTI healing which can be judged by the decrease of brous scar tissue formation, augment of brocartilaginous enthesis regeneration and better biomechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhang et al 77 demonstrated the e cacy of human embryonic MSC exosomes in promoting cartilage regeneration, and the utility of MSC exosomes as a ready-to-use and "cell-free" therapeutic alternative to cell-based MSC therapy in vivo. As for BTI healing, Wang et al 71 showed that adipose stem cell-derived Exos can decrease fatty in ltration and enhance BTI healing in vivo. In accordance with Wang et al 71 research, the present study also revealed improved BTI healing which can be judged by the decrease of brous scar tissue formation, augment of brocartilaginous enthesis regeneration and better biomechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…These cartilage protective findings of IPFP-Exos in DMM-induced OA are similar to the beneficial effects seen in a new study with ADSCs-Exos for chronic rotator cuff tears in a rabbit model, where lower fatty infiltration, more newly regenerated fibrocartilage, and improved biomechanics was seen in the ADSCs-Exos group compared to those with saline only [ 43 ].…”
Section: Resultssupporting
confidence: 79%
“…ASC–conditioned medium (ASC-CM) was used to isolate ASC-Exos by gradient ultracentrifugation as our previous studies described. 25,26 Briefly, the ASC-CM was ultracentrifuged as follows: 300 g , 10 minutes (to remove the live cell pellet); 2000 g , 10 minutes (to remove the dead cell pellet); 10,000 g , 30 minutes (to remove the cell debris pellet); 100,000 g , 70 minutes (to obtain the ASC-Exos and contaminating protein pellet); and 100,000 g , 70 minutes (to obtain the ASC-Exos pellet).…”
Section: Methodsmentioning
confidence: 99%